A distributed model to analyze QoS parameters performance improvement for fixed WiMAX networks - A. L. Ibrahim; A. Md. Said; Kashif Nisar; Peer Azmat Shah; Abubakar Aminu Mu’azu (Springer, 2014)
Quality of Service (QoS) is an important parameter that is use for evaluating Network performance. In this paper a Distributed model was developed to analyze QoS Parameters Performance Improvement for Fixed Worldwide Interoperability for Microwave Access (WiMAX) Network using parameters that include Delay, Throughput and Application Response Time to enhance the services that are provided to the end users. The designed has been evaluated using the simulation tool OPNET modeler 16.0 and compared with the Existing model which is centralized. The results obtained from the new Distributed model shows significant increase in the network throughput from 12,000bit/sec to14, 000bit/sec, and decrease in delay from 0.012sec to 0.009sec and also decrease in application response time from 0.94bit/sec to 0.69bit/sec in Scenario1. The result of the distributed model enhances the QoS performance